KAJI EKSPERIMENTAL PENGGUNAAN KAMPAS REM KOMPOSIT SERBUK BAMBU PADA SEPEDA MOTOR YAMAHA JUPITER Z - Ichsan Rusdianto; Ranto Ranto; Budi Harjanto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2020)
This study aims to (1) investigate how the value of the brake lining composite from bamboo powder when tested directly on the motorcycle, (2) investigate the comparative rate of wear of the brake lining composite from bamboo powder towards brake lining Indoparts brand. This research was conducted at the Education Building Engineering, the Faculty of Teacher Training and Education, Sebelas Maret University. The Composition of the brake lining composite from bamboo powder contains bamboo powder, Aluminium powder (Al) and Magnesium Oxide (MgO), the constituent matrix composites is Epoxy resin form which is tested using the test as far as 1500 km. In this study the sampling technique used purposive sampling. The results of this research are (1) The wear rate of the brake lining natural fiber composites from bamboo powder specimen for every 500 km are equal to 0.095 mm in the inside part and the outside part is 0.123 mm for every 500 km, (2) The wear rate of the brake natural fiber from bamboo powder for every kilometer are equal to 0,000246 mm/km and the wear rate of brake lining from Indoparts brand are equal to 0,000496 mm/km.